“A Comparative Clinical Study On The Role Of Vaman Karma And Shaman Yoga In The Management Of Yuvan Pidaka W.S.R. To Acne Vulgaris.” - Subhrajyoti, Chakraborty; S.N, Chowdhury; Shailendra, Singh; Sukumar, Ghosh (International Journal of Psychosocial Rehabilitation, 2020)
Background - Ayurveda is an ancient discipline of indigenous medicine as well as a way of life for people. Yuvan Pidaka, also known as acne vulgaris, is one of the issues that affects 85% of adolescents and young adults. It results in an ugly appearance that could affect the sufferers’ social and personal lives. Numerous herbs and mixtures are available in ayurvedic therapy to treat Yuvan pidaka. Objective - To assess the efficacy of Vamana karma and Shamana chikitsa in the management of Yuvan pidaka. Materials & methods - Total 60 patients were selected from the OPD & IPD of the Institute after getting approval from the Institutional Ethics Committee (SVP/564/2017 dated 29/5/2017). Out of 60 patients divided into two groups A & B, 30 patients were treated with Vamana karma & Dhanyakadi lepa and in another group 30 patients were treated with oral administration of Manjistha churna followed by local application of Dhanyakadi lepa. Results – Total 55 patients out of 60 patients completed the therapeutic protocol. The statistical interpretation was found highly significant in Group A patients i.e., p < 0.001in comparison to Group B patients. Conclusion – The prescribed treatment shows significant results in Yuvan pidaka and no untoward effect was noted during the period of the study. The data generated by this study will provide a new dimension in the management of Yuvan pidaka vis-à-vis Acne vulgaris.